ANALISIS MULTIVARIAT FAKTOR RISIKO METABOLIK PENYEBAB KEJADIAN STROKE (STUDI KASUS KONTROL DI PUSKESMAS KECAMATAN CEMPAKA PUTIH) - Stefanus Gardino; Yohanes Firmansyah; Murni L Naibaho (Jurnal Medika Hutama, 2022)
Stroke is one of the neurological diseases that are emergency, acute and can cause the highest number of deaths and deaths in several countries around the world. In general, the risk factors for stroke are divided into two, namely factors that can be regulated, including hypertension, diabetes mellitus, hyperuricemia, hypercholesterolemia and obesity and risk factors that cannot be determined such as age and gender. This study aims to determine the potential metabolic risk factors that cause stroke. Research method: this study is a case control study using medical record data at the Cempaka Putih District Health Center. The case samples of this study were all stroke patients aged more than 18 years diagnosed either primarily by a health center doctor, or diagnosed by a specialist or general practitioner elsewhere, while the control sample in this study were patients without a history of ischemic or hemorrhagic stroke with a minimum age of 18 years. The results of this study found a significant relationship between hypertension, diabetes, gender, occupation, marital status and age group 60 years and over on the incidence of stroke (p-value: < 0.05), and from the results of the multivariate Binary Logistic - Backward LR test, it was obtained with 5 key test stages that there are 3 dominant variables as risk factors that can be independently estimated to affect the incidence of stroke, namely hypertension, occupation, and gender.